Assessment of aged biodegradable polymer-coated nano-zero-valent iron for degradation of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) - Wazne, Mahmoud (2012)
BACKGROUND: This study reports on the effects of aging on suspension behavior of biodegradable polymer-coated nano-zero-valent iron (nZVI) and its degradation rates of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) under reductive conditions. The polymers investigated included guar gum, potato starch, alginic acid (AA), and carboxymethyl cellulose (CMC). Polymer coating was used to mitigate nZVI delivery hindrance for in situ treatment of RDX-contaminated groundwater. RESULTS: The RDX degradation rates by bare nZVI and starch-coated nZVI suspensions were least affected by aging although these suspensions exhibited the least favorable dispersion behavior. CMC, AA, and guar gum coating improved nZVI rates of degradation of RDX but these rates decreased upon aging. The best suspension stability upon aging was achieved by CMC and AA. Guar gum with loadings rates one order of magnitude lower than that of CMC and AA achieved good iron stabilization but significantly higher RDX degradation rates. CONCLUSION: It is demonstrated that both migration and reactivity of polymer-stabilized nZVI should be explicitly evaluated over a long period before application in the field. Guar gum coated nZVI appeared best suited for in situ application because it maintained good suspension stability, with RDX degradation rates least affected by aging compared with the other polymers tested. © 2012 Society of Chemical Industry